2013
DOI: 10.1021/ja4030462
|View full text |Cite
|
Sign up to set email alerts
|

A Five-Coordinate Nickel(II) Fluoroalkyl Complex as a Precursor to a Spectroscopically Detectable Ni(III) Species

Abstract: Mechanistic proposals for nickel-catalyzed coupling reactions often invoke five-coordinate alkyl- or aryl-bound Ni(II) and/or high-valent nickel(III) species, but because of their reactive nature, they have been difficult to study and fingerprint. In this work, we invoked the stabilizing properties of fluoroalkyl ligands to access such nickel species bearing ligands that are commonplace in organic coupling reactions. We show that five-coordinate Ni(II) complexes containing nickel-carbon bonds can readily be pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
91
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 54 publications
6
91
1
Order By: Relevance
“…Spectroelectrochemical EPR studies supported the intermediacy of 10, but its short-lived nature precluded any fundamental studies of its reactivity. Quite clearly, a • CF3 radical is cleaved from 10, which was shown through spin-trapping studies using PBN (N-t-Bu-α-phenylnitrone) [54].…”
Section: Studies On the Trivalent Speciesmentioning
confidence: 92%
See 1 more Smart Citation
“…Spectroelectrochemical EPR studies supported the intermediacy of 10, but its short-lived nature precluded any fundamental studies of its reactivity. Quite clearly, a • CF3 radical is cleaved from 10, which was shown through spin-trapping studies using PBN (N-t-Bu-α-phenylnitrone) [54].…”
Section: Studies On the Trivalent Speciesmentioning
confidence: 92%
“…Vicic showed that trifluoromethyl ligands can support the five-coordinate nickel(II) species 9, which can be chemically oxidized with [ferrocenium][PF6] to generate the transient nickel(III) species 10 (Scheme 8) [54]. Once formed, however, 10 undergoes a reductive homolysis of a trifluoromethyl ligand to afford the cationic nickel(II) species 11.…”
Section: Studies On the Trivalent Speciesmentioning
confidence: 99%
“…[2] To date,p alladium [2,3] and copper [2,4] catalysts have been mainly used to form ArÀR f bonds(R f = fluoroalkyl) and thus to access fluoroalkylated arenes.D espite the importance of these synthetic methods, the catalysis of the cross-coupling/fluoroalkylationo fa renes continues to attract great interest, especially the development of more sustainable catalysts based on first-row transition metals.Yet, except for copper, the use of other abundant firstrow transition metals as catalysts has been scarcely explored. [5] Recently,w er eported the nickel-catalyzed difluoroalkylation of arylboronic acids with functionalized difluoromethyl halides, [6] which represents ac ost-efficient protocol for the preparation of functionalized difluoromethylated arenes.Inspired by this preliminary study,weenvisioned the feasibility of an ickel-catalyzed fluoromethylation of arylboronic acids with al ow-cost catalyst and industrial raw material fluoromethyl halides (Scheme 1c). To the best of our knowledge,t he nickel-catalyzed direct fluoromethylation of aromatics has not been reported thus far.…”
mentioning
confidence: 99%
“…[2,3,8,9] Also in the field of organic synthesis, perfluoroorgano silver compounds attract more and more attention in the conversion of acid chlorides into perfluoroorgano ketones, [10,11] in the copper-mediated trifluoromethylation of aryl halides, [12,13] in C-H fluoroalkylation of differently substituted aromatic substrates, [14][15][16] or in the conversion of diazonium salts into trifluoromethyl-substituted aromatics. [17] Earlier studies [18] revealed that in solution especially perfluoroalkylsilver derivatives undergo complex exchange equilibria involving a "neutral" species, AgR f , an "ionic" species, Ag[Ag(R f ) 2 ], and a "polymeric" form, [ 4-Dimethylaminopyridine (DMAP), additionally to its excellent catalytic activity in organic transformations, [19] exhibits positive features making among many other metal compounds silver derivatives easily crystallizable.…”
Section: Introductionmentioning
confidence: 99%
“…[2,22,23] Also the number of publications dealing with structurally characterized perfluoroarylsilver(I) derivatives is low. [7][8][9] With the aim to obtain perfluoroorgano silver(I) compounds of high stability and low sensitivity against moisture expecting them to become suitable precursors for the deposition of silver nanoparticles or shelf-stable reagents for transformations in metalorganic or organic synthesis, the behavior of AgR f (R f = CF 3 , C 2 F 5 , C 6 F 5 ) in reactions with DMAP was investigated.…”
Section: Introductionmentioning
confidence: 99%